Improvement of a Simulink model and graphical user interface for a robotic foot testing equipment - Jiang, Fuming (Nanyang Technological University, 2022)
A mechanical footwear device is one of the primary approaches to evaluate the variety of performances of sports shoes. Appropriate mechanical structure and rational electronic & control system contribute to its accurate operation. This project aims to update the control system of an existing robotic foot testing (RFT) equipment. This RFT equipment simulates human running with the dSPACE controller and a Simulink model, which can test sneakers' durability and slip resistance. Due to some hardware optimizations and sensor changes, the existing Simulink model needs to be refined to adapt to the current RFT equipment. Meanwhile, this project also aims to update the graphical user interface (GUI) of the RFT, enabling it to work with updated Simulink models.